외식산업의 인터넷마케팅 효과에 관한 연구 -대전사랑 외식산업회원 사례연구 - 전영직; Jeon, Young-Jick (한국콘텐츠학회 논문지, 9(11), 2009)
The research under necessary for systematic study is about recognizing on the Internet marketing in the Food Service Industry. After searching the actual condition with the object of the Lovedaejeon 'Foodservice member, the goal is using fundamental data for strategic marketing plan making systematic Internet marketing in the Food Service area. Analytical result, the influx search which finds the Lovedaejeon 'Foodservice is 3 kinds to be highest : Daejeon, the Daejeon tasty house and fixation keyword of tasty house etc. As for visit area, Daejeon 47.9%, Re-visit 31.9% of 12 hours within re-visit. From tasty house coupon down load, 친친만년점 restaurant 1,837 and from member connection statistics of man and woman, the man is higher than the woman statistically, the marriaged man was higher than the single one. Like this research result, there will be a possibility becoming the fundamental data which is useful in Food Service Industry on the Internet marketing. 본 연구는 외식산업에 있어서 인터넷마케팅에 대한 체계적인 연구가 필요하다는 인식하에 대전사랑 맛집 회원을 대상으로 실태를 파악하고 외식업체들의 체계적인 인터넷 마케팅 전략을 수립하는데 있어 기초적 자료로 활용하는데 목적을 두었다. 분석결과 대전사랑 맛집을 찾는 유입검색은 대전, 대전맛집, 맛집 등 3가지의 고정식 키워드가 가장 높았으며, 방문지역으로서는 대전 47.9%, 재방문경과는 12시간이내 재방문 31.9%. 맛집 쿠폰 다운로드에서는 친친만년점 레스토랑 1,837건 남녀의 회원접속 통계에서 여성보다는 남자가 통계적으로 높았으며 기혼보다는 미혼에 대한 접속이 높았다. 이러한 연구결과는 외식산업 인터넷마케팅 시장세분화에 유용한 기초자료가 될 수 있음을 확인하였다.